Algorithm of calculation of electromagnetic coupling coefficient of antennas of airplane radio-electronic facilities - Іванов, В. О.; Моргун, О. А. (Proceedings of National Aviation University, 2021)
It is offered the general algorithm of calculation of electromagnetic coupling unforeseen coefficient between airplane antennas independently of their types, positions and operation frequencies. It is adduced formulas for calculation of certain intermediate indexes, which are used in corresponding stages of algorithm realization.